Question
upstudy study bank question image url

Activity - Given: \( f(x)=-x+2, \quad g(x)=2 x^{2}-1, \quad h(x)=\frac{1}{x} \) Determine: \( \begin{array}{lllll}\text { a) } f(-1) & \text { b) } g(a) & \text { c) } h\left(\frac{1}{2}\right) & \text { d) } f(a+2) & \text { e) } f(a)+g(a)\end{array} \quad \) f) \( h\left(\frac{1}{x}\right) \) \( \begin{array}{llll}\text { E) } g(-2)+h(2)-f(3) & \text { h] } f(x) \times g(0) & \text { i) } f[g(0)] & \text { ] } g[h(-2)]\end{array} \)

Ask by Franklin Maxwell. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( f(-1) = 3 \) b) \( g(a) = 2a^2 - 1 \) c) \( h\left(\frac{1}{2}\right) = 2 \) d) \( f(a + 2) = -a \) e) \( f(a) + g(a) = 2a^2 - a + 1 \) f) \( h\left(\frac{1}{x}\right) = x \) (for \( x \neq 0 \)) E) \( g(-2) + h(2) - f(3) = \frac{17}{2} \) h) \( f(x) \times g(0) = x - 2 \) i) \( f[g(0)] = 3 \) ] \( g[h(-2)] = -\frac{1}{2} \)

Solution

We are given the functions   f(x) = –x + 2   g(x) = 2x² – 1   h(x) = 1/x Below are the steps to compute each part. ────────────────────────────── a) f(–1) f(–1) = –(–1) + 2      = 1 + 2      = 3 ────────────────────────────── b) g(a) Replace x by a: g(a) = 2(a)² – 1      = 2a² – 1 ────────────────────────────── c) h(½) h(½) = 1/(½)      = 2 ────────────────────────────── d) f(a + 2) f(a + 2) = –(a + 2) + 2      = –a – 2 + 2      = –a ────────────────────────────── e) f(a) + g(a) First, find f(a) and g(a) separately:  f(a) = –a + 2  g(a) = 2a² – 1 Now add: f(a) + g(a) = (–a + 2) + (2a² – 1)          = 2a² – a + 1 ────────────────────────────── f) h(1/x) Replace x by 1/x in h(x): h(1/x) = 1/(1/x)      = x             (provided x ≠ 0) ────────────────────────────── Next, we have additional expressions: ────────────────────────────── E) g(–2) + h(2) – f(3) First, compute each term:  • g(–2) = 2(–2)² – 1 = 2(4) – 1 = 8 – 1 = 7  • h(2) = 1/2  • f(3) = –3 + 2 = –1 Now, combine: g(–2) + h(2) – f(3) = 7 + (1/2) – (–1)              = 7 + 1/2 + 1              = 8 + 1/2              = 17/2 ────────────────────────────── h] f(x) × g(0) First, compute g(0):  g(0) = 2·0² – 1 = –1 Now, multiply by f(x): f(x) × g(0) = f(x) × (–1) = –f(x) Since f(x) = –x + 2, we have: –f(x) = –(–x + 2) = x – 2 ────────────────────────────── i) f[g(0)] Since we already found g(0) = –1, then f[g(0)] = f(–1) = 3        (as computed in part a) ────────────────────────────── ] g[h(–2)] First, find h(–2):  h(–2) = 1/(–2) = –½ Now, compute g(–½):  g(–½) = 2(–½)² – 1 = 2(¼) – 1 = ½ – 1 = –½ ────────────────────────────── Final Answers Summary: a) f(–1) = 3 b) g(a) = 2a² – 1 c) h(1/2) = 2 d) f(a + 2) = –a e) f(a) + g(a) = 2a² – a + 1 f) h(1/x) = x         (x ≠ 0) E) g(–2) + h(2) – f(3) = 17/2 h] f(x) × g(0) = x – 2 i) f[g(0)] = 3 ] g[h(–2)] = –½ Any answer written in equivalent form is correct.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Let's dive into these functions and see what we can find! For \( f(-1) \), we plug in \(-1\) into \( f(x) = -x + 2 \). Thus, \( f(-1) = -(-1) + 2 = 1 + 2 = 3 \). Next, for \( g(a) \), we use \( g(x) = 2x^2 - 1 \). Therefore, \( g(a) = 2a^2 - 1 \). Now, substituting for \( h\left(\frac{1}{2}\right) \) using \( h(x) = \frac{1}{x} \), we have \( h\left(\frac{1}{2}\right) = \frac{1}{\frac{1}{2}} = 2 \). For \( d) \) \( f(a+2) \), we substitute \( a+2 \) into \( f(x) \): \( f(a+2) = -(a+2) + 2 = -a - 2 + 2 = -a \). For \( e) \) \( f(a) + g(a) \), we already calculated \( f(a) = -a + 2 \) and \( g(a) = 2a^2 - 1 \), so adding those gives us \( (-a + 2) + (2a^2 - 1) = 2a^2 - a + 1 \). For \( f(g(0)) \), we need \( g(0) = 2(0)^2 - 1 = -1 \), which means we need to find \( f(-1) \). Since we calculated \( f(-1) = 3 \), we have \( f(g(0)) = 3 \). Next is \( g[h(-2)] \). First, we need to find \( h(-2) = \frac{1}{-2} = -\frac{1}{2} \), then \( g\left(-\frac{1}{2}\right) = 2\left(-\frac{1}{2}\right)^2 - 1 = 2 \cdot \frac{1}{4} - 1 = \frac{1}{2} - 1 = -\frac{1}{2} \). Lastly, let’s check \( g(-2) + h(2) - f(3) \): - \( g(-2) = 2(-2)^2 - 1 = 8 - 1 = 7 \) - \( h(2) = \frac{1}{2} \) - \( f(3) = -3 + 2 = -1 \) So, combining them gives: \( 7 + \frac{1}{2} - (-1) = 7 + \frac{1}{2} + 1 = 8.5 \) or \( \frac{17}{2} \) in fractional form. So here are your answers summarized: - \( f(-1) = 3 \) - \( g(a) = 2a^2 - 1 \) - \( h\left(\frac{1}{2}\right) = 2 \) - \( f(a+2) = -a \) - \( f(a) + g(a) = 2a^2 - a + 1 \) - \( h\left(\frac{1}{x}\right) = x \) - \( g(-2) + h(2) - f(3) = \frac{17}{2} \) - \( f[g(0)] = 3 \) - \( g[h(-2)] = -\frac{1}{2} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy